2014
DOI: 10.1155/2014/534534
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Correlation between IL-28B Gene Polymorphisms and the Clinical Presentation of Chronic Hepatitis B in an Amazon Brazilian Population

Abstract: Objective. The present study investigated the prevalence of the IL-28B polymorphisms rs12979860 and rs8099917 in chronic hepatitis B patients from a case study in Eastern Amazonia. Methods. In total, 65 chronically infected HBV patients and 97 healthy subjects who were anti-HBc and anti-HBs positive (control group) were evaluated between May 2011 and December 2012. The groups of patients were designated as inactive carriers, chronic hepatitis without cirrhosis, and chronic hepatitis with cirrhosis based on cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Also, the data reported by Martin-Carbonero et al ( 38 ) and Martin et al ( 33 ) indicated no differences between the allelic and genotypic frequencies of the rs12979860 polymorphism of two groups. Consistent with our study, in the studies that have been conducted in Brazil ( 39 ) and USA ( 33 ), a slight predominance of the C allele was found. Also, no correlation was found between CC genotype and clinical outcome in Asian chronic hepatitis B patients, both HBeAg-positive and negative ( 40 ).…”
Section: Discussionsupporting
confidence: 92%
“…Also, the data reported by Martin-Carbonero et al ( 38 ) and Martin et al ( 33 ) indicated no differences between the allelic and genotypic frequencies of the rs12979860 polymorphism of two groups. Consistent with our study, in the studies that have been conducted in Brazil ( 39 ) and USA ( 33 ), a slight predominance of the C allele was found. Also, no correlation was found between CC genotype and clinical outcome in Asian chronic hepatitis B patients, both HBeAg-positive and negative ( 40 ).…”
Section: Discussionsupporting
confidence: 92%
“…In Brazil, this association was observed by Ramos et al 29 and Garcia et al 30 who reported an association with spontaneous viral clearance in hepatitis C infection. However, it was not observed by Ferreira et al 31 and Conde et al, 32 two other works made in Brazil. Grandi et al 33 in a population from south Brazil reported that the rs12979860 CC genotype was significantly associated with higher treatment response rates and a lower relapse rate compared to other genotypes.…”
Section: Discussionmentioning
confidence: 77%
“…Some studies did not find significant relationship between IL-28B SNPs and HBV susceptibility (Da Silva Conde et al, 2014;De Niet et al, 2012;Heidari et al, 2016;Holmes et al, 2013;Kandemir et al, 2013;Kim et al, 2013;Lee et al, 2013;Li et al, 2011;Martin-Carbonero et al, 2012;Martin et al, 2010;Ochi et al, 2011;Seto et al, 2013;Tseng et al, 2011;Zhang et al, 2014a). In contrast, other studies showed some favorable genotypes that can predict virological and serological responses in HBeAg-negative and/or positive patients (Lampertico et al, 2013;Seto et al, 2013;Sonneveld et al, 2012;Wu et al, 2012).…”
Section: Il-28bmentioning
confidence: 99%
“…Tseng et al, 2006) −1082 A/G, −819 T/C, −592 A/C RISK(Miyazoe et al, 2002;Peng et al, 2006;Shin et al, 2003a −819 T/C, −592 A/C RISK(Saxena et al, 2014a) IL-28B rs12979860C/T, rs8099917G/T NS (Da SilvaConde et al, 2014;De Niet et al, 2012;Heidari et al, 2016;Martin-Carbonero et al, 2012) rs12979860C/T NS(Holmes et al, 2013;Kandemir et al, 2013;Martin et al, 2010;Peng et al, 2012;Sonneveld et al, 2012;Zhang et al, 2014a) rs12979860, rs12980275 and rs8099917 PROTECTION (Li et al, 2011) rs12979860, rs12980275 and rs8099917 NS (Kim et al, 2013; Lee et al, 2013) rs12979860C/T, rs8099917G/T PROTECTION (Seto et al, 2013) rs8099917G/T PROTECTION (Wu et al, 2012) rs12979860C/T PROTECTION (Lampertico et al, 2013) rs12979860, rs12980275, rs8105790 PROTECTION (Al-Qahtani et al, 2014) rs12979860C/T RISK (Chen et al, 2012) rs8099917G/T RISK (Li et al, 2012) TGF-β −509C/T, +915G/C NS (Hosseini Razavi et al, 2014) −509C/T, −800G/A, −988C/A NS (Yang et al, 2005) −509C/T PROTECTION (Kim et al, 2003a; Qi et al, 2009; Saxena et al, 2014b) −800GNA, −509CNT, Leu10Pro and Arg25Pro RISK (Falleti et al, 2008) IFN-γ +874A/T RISK (Ben-Ari et al, 2003; Saxena et al, 2014c) +874A/T NS (Cheong et al, 2006b) +874A/T, +2109A/G RISK (Liu et al, 2006a) IFN-γ +874 and IFNGR-1 (−56 and −611) RISK (Korachi et al, 2013) TNF-α −308 G/A, −238 G/A RISK (Zhang et al, 2011a) −238 G/A RISK (HOHLER et al, 1998a; Lu et al, 2004; Zheng et al, 2012) −863C/A RISK (Kummee et al, 2007) −857C/T PROTECTION (Shi et al, 2012) −857C/T, −308 G/A PROTECTION (Zhang et al, 2014b) −238 G/A, −308 G/A RISK (Cheong et al, 2006a) rs361525, rs1800629, rs1799724, rs1800630 and rs1799964 RISK (Fletcher et al, 2011) −1031TNC, −863CNA, −857CNT, −376GNA, −308GNA, −238GNA and −163GNA RISK/PROTECTION (Kim et al, 2003b) −238G/A, −308G/A, −857C/T, −863C/A, −1031T/C RISK/PROTECTION (Du et al, 2006) −308G/A NS (Somi et al, 2006) MIF MIF-173 G/C RISK (Zhang et al, 2013) HLA DRB1PROTECTION(Hohler et al, 1997;Thio et al, 2003;Thursz et al, 1995) DQA1, DQB1 PROTECTION (Thio et al, 1999) DPA1 and DPB1 RISK/PROTECTION (Guo et al, 2011; Kamatani et al, 2009) DPA1 and DPB1 PROTECTION (Nishida et al, 2012) DR13 PROTECTION (Diepolder et al, 1998) HLA-B35, HLA-CW4, HLA-DQ2, and HLA-DQ8 RISK/PROTECTION (Albayrak et al, 2011) HLA (A, B, DRB1) RISK/PROTECTION (Wu et al, 2004) HLA-C, HLA-DP and HLA-DQ. PROTECTION (Hu et al, 2013) Chemokines CCR5-D32 RISK (Suneetha et al, 2006) CCR5-D 32 NS (Ahn et al, 2006; Chang et al…”
mentioning
confidence: 99%